Task collection monitoring system on lockers with notifications on Telegram - Rahmat Novrianda Dasmen; Sandy Prayitno (Program Studi Teknik Elektro Universitas Khairun, 2023)
In this new normal era, universities, both private and public, have started to learn face-to-face. When collecting assignment reports, sometimes teachers or lecturers are unable to attend because of the hectic activity of activities, sometimes there are students who lie or cheat when submitting assignments. Therefore, making a place or safe for collecting assignments that aims to make it easier for teachers to collect assignments that have been given. The safe is designed using an Arduino microcontroller which functions to integrate components such as RFID sensors, finger print, ultrasonic, LCD and ESP32Cam modules. RFID sensors are use to identify a student’s data. The ESP32Cam module is used to take pictures of students’ photos when submitting assignments. Student photos will be sent directly to the teacher’s or lecture’s telegram application. The ultrasonic sensor is used to determine the contents of the safe, if the safe is full the ultrasonic sensor will work and the buzzer will sound. As a security, the safe uses a finger print that can only be accessed by the lecturer or teacher.